African and africanized tissues in candomblés of São Paulo (Revista de Ensino em Artes, Moda e Design, 2021)
The fabrics that come from Africa are fundamental for thinking about the aesthetics ofcandomblés of São Paulo, as their historical trajectories demonstrate a complex cultural plotthat questions the notion of pure origin, while still being used as symbols of African and Afro-Brazilian cultural identity. This work seeks to analyze the motivation for the use of fabricscoming from the Africa, within the candomblés of São Paulo, until today. The objective is tobring the history of these fabrics from the African continent, until their arrival in candomblés:the Așǫ Oke, produced by the yorùbá; the industrially Wax Print; and Nigerian-Austrian laces.We sought to identify the presence of these textiles through images of the twentieth century,and visits to temples in São Paulo, for analysis in the contemporary. What were discoveredwere distinct processes that motivated this use: Wax Print gained a load of connection withwhat is being worn on the African continent today. Așǫ Oke is related to the idea of tradition.While the laces imported from Nigeria are consumed, mixing an allusion to the clothing ofCreoles, with the contemporary import of fabrics that pass through the African continent.The greatest difficulty of the research was to find the confluences of narratives of the fabricproducers and users; in addition to the few Brazilian researchers who have analyzed thetextiles. Finally, the importance of this research lies in a new analysis of these textiles, incontext of candomblés, verifying them as an inseparable part of the aesthetics that makeup the ethos of the people of axé.
Keywords: Așǫ Oke; Wax Print; African Lace